Entrepreneurial intention among undergraduate agricultural students in the Republic of Benin - Kaki, R.S.; Mignouna, Djana B.; Aoudji, K.N.A.; Adeoti, A. (Informa UK Limited, 2023)
In sub-Saharan Africa, where the professional insertion of graduates remains a major challenge, entrepreneurship represents an alternative to youth unemployment. This study investigates the predictors of agribusiness entrepreneurial intentions amongst undergraduate agricultural students in the Republic of Benin. A sample of 351 final year agricultural students was selected from universities. The data were collected through structured questionnaire and analyzed using descriptive statistics and a binary logistic regression. The findings showed that 44.16% of respondents were willing to start their own agribusiness venture after graduation with a preference for agro-processing enterprises (35.48%) and crop production enterprises (26.45%). The significant factors that influence agricultural students’ entrepreneurial intention in agribusiness were age, their major field of study, type of university attended, previous experience in agribusiness, a role model as a friend, and perception of agribusiness environment. The study suggests the establishment of clubs for agribusiness entrepreneurship in agricultural faculties and universities; showcasing of young entrepreneurs in agribusiness through national competitions, and events, such as “Agri-Enterprise Week” at universities, inviting young agribusiness entrepreneurs to share their experiences with the students in the next generation as guests lecturer; and the creation by the government of a conducive agribusiness environment for youth graduates. In the light of these insights, several paths for future research emerge.